Kegiatan Ekstrakurikuler Tembang Batang Hari Sembilan di SMK Negeri 1 Tulung Selapan - Abim Septiadi; Deria Sepdwiko; Auzy Madona Adoma (Departement of Mathematics Education, 2024)
The background of this research is how the extracurricular activities of the ninth day of Tembang Batang at SMK Negeri 1 Tulung Selapan. This study aims to find out and describe how the process of extracurricular activities of the nine days of tembang stems at SMK Negeri 1 Tulung Selapan. The method in this study applies a qualitative descriptive method with data collection techniques applying triangulation of three data sources, namely observation, interviews, and documentation. The results of the study showed that the nine-day tembang stem extracurricular activity at SMK Negeri 1 Tulung Selapan was going well, but only a few students took part in the nine-day tembang stem extracurricular activity, this was due to the lack of student motivation in learning regional music and the level of difficulty playing the nine day songs also made some students decide not to participate in the extracurricular activities of the nine day songs at SMK Negeri 1 Tulung Selapan. The extracurricular song stems day nine was attended by 3 students consisting of 2 boys and 1 girl, the initial activity started with the teacher explaining the meaning, history and main elements of song stems day nine, followed by learning the basic techniques of playing the guitar, then studied the art of Tembang Batang Hari Sembilan with the songribulahhribu. At the end of the lesson, the teacher gave a test forwork, namely playing the songribulahribu, and as a result, students got very good grades. This shows that the extracurricular activities of the nine days of Tembang Batang at SMK Negeri 1 Tulung Selapan have gone well, it's just that there is a lack of student motivation in learning regional music and the difficulty level of playing the guitar in the art of Tembang Batang these nine days which causes only a few students to take part in the extracurricular songs. stem of day nine at SMK Negeri 1 Tulung Selapan.